Clinical profile of Wilson Disease with Neurological Presentations : A cross sectional study in Bangladesh perspective - Fatema, Kanij; Rahman, Md Mizanur; Hossain, Mohammad Monir; Begum, Fahmida; Islam, Kazi Ashraful; Akhter, Shaheen (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Objective: Wilson Disease (WD) of neurological presentation is rare in pediatric population . Very limited study has been done in this disorder particularly from Bangladesh. This study was done to describe clinical profile of children with Wilson Disease with neurological presentation. Methods: This cohort study was conducted in the Department of Pediatric Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), from July 2018 to July 2021. Children under 18 years of age having either neurological or combined hepatic and neurological features of WD were included. Results: Total 74 patients were taken as study case. A male predominance was observed. Age of presentation was comparatively late in neuro-hepatic group. Jaundice and cirrhosis of liver was observed in more than two third cases of neuro-hepatic group. Most of the patients of both group presented with deterioration of school performance (100% and 88.89%, respectively), dystonia (95% and 75.63%, respectively), drooling (85% and 75.93%, respectively), altered activity of daily living (85% and 77.78%, respectively), dysphasia (95% and 81.48%, respectively). Patients with neuro-hepatic manifestations had significantly lower serum ceruloplasmin and serum albumin while that of urinary total copper excretion was significantly higher in this group. In MRI of brain, most affected parts were putamen, head of caudate nucleus and thalamus. Conclusion:. The most important clinical features school performance deterioration, dystonia, impaired daily activity and jaundice. Patients with neuro-hepatic features had lower serum ceruloplasmin and higher urinary total copper. In MRI, most affected part was putamen, thalamus and head of caudate nucleus. Most patients showed some improvement or remained stable after treatment. J Bangladesh Coll Phys Surg 2024; 42: 265-272